Relationship Between Medication Literacy and Frailty in Elderly Inpatients With Coronary Heart Disease: A Cross-Sectional Study in China - Qu, Jiling; Zhou, Ting; Xue, Mengxin; Sun, Huiping; Shen, Yijing; Liu, Yongbing (Frontiers in Pharmacology, 2021)
Background: Mastering medication literacy may be related to medication safety, and the identification of frailty is very important for the prognosis of coronary heart disease (CHD). Few studies have examined the relationship between medication literacy and frailty in patients with CHD. The aim of this study was to investigate the state of medication literacy and frailty in patients with CHD and to explore the relationship between medication literacy and frailty. Methods: A cross-sectional investigation evaluated 295 inpatients with CHD recruited from hospitals in Yangzhou, China. Demographic and clinical data on participants were collected using a general information questionnaire. The Chinese medication literacy scale was used to evaluate medication literacy. The Fried Frailty Phenotype scale was used to evaluate frailty. Univariate analysis employed chi-square test and Kruskal-Wallis H test to examine the potential factors affecting frailty. Taking frailty status as the outcome variable, the ordered logistic regression model was used to analyze the relationship between the degree of medication literacy and frailty. Spearman’s correlation analysis was used to analyze the correlation between medication literacy and frailty. Results: A total of 280 elderly CHD inpatients were included in the analysis. There were 116 (41.4%) individuals with inadequate medication literacy and 89 (31.8%) frail individuals. Ordered logistic regression analysis showed that the age (p < 0.001, OR = 1.089), Charson Comorbidity Index (p = 0.029, OR = 1.300), number of medications taken (p = 0.012, OR = 1.137), and medication literacy (p < 0.05, OR > 1) were independent predictors of debilitating risk factors. The population with inadequate medication literacy had a 2.759 times greater risk of frailty than adequate medication literacy (p < 0.001, OR = 2.759); The population with marginal medication literacy had a 2.239 times greater risk of frailty than adequate medication literacy (p = 0.010, OR = 2.239). Spearman’s correlation analysis showed that the medication literacy grade was associated with the frailty grade in elderly CHD patients (R = -0.260, p < 0.001). Conclusion: The study showed a significant correlation between medical literacy and frailty in patients with CHD. The results suggested that medication literacy was an important consideration in the development, implementation, and evaluation of frailty.